Molecular studies on Cryphonectria parasitica isolates from Carpathian-basin - Irinyi, László; Görcsös, Gábor; Radócz, László (Acta Agraria Debreceniensis, 2011)
Chryphonectria parasitica, the casual agent of chestnut blight, is one of the most important fungal pathogens of chestnut (Castanea spp.) in Europe and Hungary. In this study we analyzed the diversity of 14 Cryphonectria parasitica strains isolated from different location of Carpathian-Basin. For the analyses we used the partial sequences of the translation elongation coding gene, tef1. Our results showed that the tef1 gene, contrary to other fungal species, is not suitable for the molecular analyses of C. parasitica. In the future, for the molecular studies of C. parasitica, we need to use other molecular markers like microsatellites.